Knowledge and perceptions regarding climacteric among rural women in Jammu District of UT of J and K, India: A cross-sectional study - Kiran Bala; Riya Gupta; Rajiv Kumar Gupta; Najma Akhtar (Wolters Kluwer Medknow Publications, 2022)
Background: The word Climacteric is shrouded in a culture of silence in our country, more so in the vast rural swathes of India. This survey was carried out to assess the knowledge and perceptions regarding climacteric in rural females of the Jammu district. Materials and Methods: The present study was conducted in the Kot-Bhalwal health block of Jammu district. A sample of 215 was calculated assuming a minimum prevalence of 65% of menopausal symptoms. Using a two-step simple random sampling technique, a total of 245 postmenopausal women from four villages of the health block were interviewed using a semi-structured questionnaire. Results: Among the sources of information about climacteric, family and friends were prime sources followed by community elders. About one-third (35.10%) of the respondents had no discussion about climacteric with anyone. The majority of the participants had a positive perception of climacteric and described it as a feeling of relief. About 77.9% of study participants rated their health as poor to fair. However, about one-fourth of women had taken health checkups for menopause-related symptoms. None of the respondents had any clue about oncological screening. Conclusion: Despite positive perceptions, there is a need to dispel the misconceptions with rigorous awareness and counseling. The role of village-level health workers along with ANM at Sub Health Centers/Health and wellness centers is the game-changer in this context. Every opportunity including Antenatal clinics should be utilized to educate as well as screen menopausal females for various health problems.